Assessing spatially multistage carbon transfer in the life cycle of energy with a novel multi-flow and multi-node model: A case of China's coal-to-electricity chain. (10th March 2022) - Li, Junjie; Tian, Yajun; Zhang, Yueling; Xie, Kechang
Abstract: Fully assessing the spatial carbon transfer associated with energy production and consumption activities helps to better understand the drivers of related carbon emissions and clarify the corresponding carbon reduction responsibility. However, previous work based on the single network method and input-output analysis is not ideal for boundary integrity, data reliability, or scale generality. Here, an original multi-flow and multi-node model is proposed, taking the coal-to-electricity chain as an example to explain how to address these challenges. The model ingeniously integrates the trade network of coal used for electricity generation and the transmission network of coal power to compose a spatialised coal-to-electricity chain, to address how embodied carbon emissions are transferred successively in geography. This is applied to a Chinese case to demonstrate its scientificity and advancement. The results show that 118.3 Mt CO2 eq and 598.8 Mt CO2 eq of carbon are interprovincially transferred due to coal trade and electricity transmission, respectively. The two-stage carbon transfer leads to a significant difference of 504.7 Mt CO2 eq in production- and consumption-based carbon accounting. If the embodied carbon emissions in the coal trade are not accounted, a total of 237.0 Mt CO2 eq of embodied carbon emissions would be omitted. Only a small part of carbon transfer with coal trade undergoes a secondary transfer with electricity transmission, accompanied by a small amount of carbon reflux or exchange, which is suggested to optimise the spatial pattern of the coal-to-electricity chain in a targeted manner. The proposed multi-flow and multi-node model is flexible in sectoral and spatial scales and its design idea can also help other energy activities to fully assess carbon transfer. Highlights: A novel multi-flow and multi-node model is developed to track carbon transfer. Difference in production- and consumption-based accounting reaches 504.7 Mt CO2 eq. Carbon accounting omissions reach 237.0 Mt CO2 eq if using the single network method. Carbon secondary transfer, reflux, and exchange are discovered.